Diseño y validación de protocolos soporte para la propuesta de ajuste y correlación del ICA/IACAL establecidos por el IDEAM para las eras y su aplicación en la cuenca media del río Bogotá (2014)
This project is a contribution to the Regional Water Assessment (ERA) established in Decree 1640 of 2012 that is being carried out by the CAR, since it contributes to define a proposal accompanied with its respective protocol, for the adjustment of the indicators of quality and pollution pressure of water resources, the ICA and the IACAL. The methodologies defined and developed for these indexes by the IDEAM at national level in order to generate knowledge about the state of water resources at regional level in terms of quality, were applied in the upper and middle basin of the Bogota River and the results served as a key reference for the analysis that led to the need to modify these methodologies. This document represents then, based on a series of conceptual and methodological analyses developed by the CAR for the ERAS, the regional adjustment of the calculation of the two water quality indicators and the modeling of the proposal in the Middle Basin of the Bogota River, in such a way as to reflect the status and alteration of water quality according to the management instruments used by the environmental authorities: quality objectives and decontamination or pollutant load targets. In addition, the correlation between the two indexes, with the purpose of indicating, within the framework of the integral management of water resources, the effect generated by the measures adopted by the corporation and the users discharging wastewater of punctual type, on the quality of the water by the water units of analysis identified and selected for the ERAS. Likewise, to take advantage of the process as part of the information that will feed the environmental information system, responsibility of the Regional Environmental Authorities, specifically that of the water resource (SIRH), as established by Decree 1323 of 2007.